Sosialisasi Perencanaan Karir dan Pelatihan Keterampilan Menyulam menjadi Prakarya yang Bernilai di Gampong Kuta Alam - Rahmat, Muarrief; Zulfadhli, Zulfadhli; Wahdani, Nurul; Malis, Yulisa; Zahira, Zikra Miraan; Fitria, Ria (LSM Catimore dan Sahabat, 2025)
Career planning outreach activities and embroidery training in Gampong Kuta Alam aim to provide the community with a better understanding of the importance of planning their career future. Apart from that, embroidery training is held as an effort to equip participants with skills that can be used as independent business opportunities. In its implementation, this activity adopted a community development approach, where USK FKIP Pre-Service PPG students acted as facilitators. Through the socialization carried out, participants gain insight into the steps that need to be taken in planning an effective career, while embroidery training provides practical skills that have economic value. The results of the activity showed an increase in participants' awareness of the importance of career planning, as well as high public interest in learning embroidery skills. Apart from that, this training also increases residents' self-confidence to start small businesses based on manual skills. The Keuchik of Gampong Kuta Alam appreciates this initiative and encourages the formation of an embroidery community as part of the community's economic empowerment program. So that the benefits are wider, it is hoped that there will be further support from educational institutions and the government. Overall, this activity has a real impact in improving community welfare through skill development and more structured career planning.